The Influence of Reward, Punishment, Organizational Commitment and Work Motivation towards Employee Performance - Agustin Hari Prastyowati; Nasution Bin Ismail; Musaiyadi Musaiyadi (ABM: International Journal of Administration, Business and Management, 2023)
This study aims to analyze the influence of rewards, punishments, organizational commitment, and work motivation on employee performance at the Department of Agriculture and Food Security of Bondowoso Regency. The research method used a quantitative approach with OLS-based multiple linear regression analysis. A sample of 105 respondents was selected through purposive sampling, with criteria of a minimum of three years of service and civil servant status. The results showed that rewards, organizational commitment, and work motivation significantly influenced employee performance, while punishment had no significant effect. Simultaneous tests showed that all four variables together contributed significantly to improving employee performance, with work motivation being the dominant factor. The research discussion confirms that appropriate rewards, commitment to the organization, and strong motivational drive can increase employee productivity and loyalty. Conversely, punishment proved less effective because it did not always encourage positive changes in work behavior. A unique finding of this study was the insignificance of the punishment variable on performance, indicating that the sanction approach is irrelevant in the context of Bondowoso's public bureaucracy, and work motivation emerged as the primary determinant of performance improvement.